Private Experience and Public-Spirited Critique: Brexit-Era Britain in the Recent Poetry of Vidyan Ravinthiran and Nicholas Hagger - Pomeroy, Jeremy (Porównania, 2021)
Two starkly different aspects of the Brexit phenomenon may be seen in the recent work of two British poets, Vidyan Ravinthiran and Nicholas Hagger. Ravinthiran’s most recent book consists of love sonnets composed for his wife. These are addressed to an intimate “you” which, upon publication, is expanded to vicariously include his readership. In the course of their everyday life as a mixed-race couple in northern England, the context of Brexit occasionally intrudes. When it leads him to communicate something to his wife, the poet organically transcribes these experiences. While ultimately a secondary (if often inescapable) theme in Ravinthiran’s sonnet sequence, the Brexit negotiations are the leitmotif of Hagger’s Fools’ Paradise. Taking his cue from the sixteenth and seventeenth century mock epic, the poet offers an erudite satire excoriating a short-sighted political class. Hagger appears to move easily in such circles, presumably due to the diplomatic and intelligence contacts in his past. Assuming the guise of an insider or pundit, “your poet” provides a meticulous, tactical critique of the inefficacy of foolish parliamentarians.